2018
DOI: 10.4236/iim.2018.105010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Several Data Mining Methods in Credit Card Default Prediction

Abstract: LightGBM is an open-source, distributed and high-performance GB framework built by Microsoft company. LightGBM has some advantages such as fast learning speed, high parallelism efficiency and high-volume data, and so on. Based on the open data set of credit card in Taiwan, five data mining methods, Logistic regression, SVM, neural network, Xgboost and LightGBM, are compared in this paper. The results show that the AUC, F 1-Score and the predictive correct ratio of LightGBM are the best, and that of Xgboost is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 3 publications
(2 reference statements)
0
11
0
1
Order By: Relevance
“…After that the golden, bronze, silver and classic clusters with 5580, 5171, 6832 and 5858 customers respectively. Table 5 shows that by comparing our results with paper [7], [22]- [24]; we found that our proposed model achieved the best result in the accuracy measures. The earlier researches we have found using the same dataset and the same technique (ANN).…”
Section: ) Neural Network Evaluationmentioning
confidence: 72%
See 1 more Smart Citation
“…After that the golden, bronze, silver and classic clusters with 5580, 5171, 6832 and 5858 customers respectively. Table 5 shows that by comparing our results with paper [7], [22]- [24]; we found that our proposed model achieved the best result in the accuracy measures. The earlier researches we have found using the same dataset and the same technique (ANN).…”
Section: ) Neural Network Evaluationmentioning
confidence: 72%
“…In 2018, Yang and Zhang [7] presented a classification model for the credit card default data set in the bank from Taiwan using five clustering algorithms. 10-fold cross-validation was used to get the average area under the curve (AUC) and the correct rate of the model.…”
Section: Literature Surveymentioning
confidence: 99%
“…General Terms Pattern Recognition, Medical Image Processing. [8] demonstrates that LightGBM or Xgboost has a decent presentation in the expectation of clear-cut reaction factors and has a decent application esteem in the huge information period. The examination of models with boosting and smoothing shows that blunder rate is preferred measurement over region under bend (AUC) proportion.…”
Section: Literature Surveymentioning
confidence: 99%
“…Based on the data at hand, the prediction of perceived age and health is a supervised learning problem and more specifically a regression problem. Therefore, we decided to use the gradient boosting framework Light Gradient Boosting Machine (lightGBM) developed by Microsoft, which has been shown to outperform other gradient boosting frameworks and even neural networks under specific condition [18][19]. We used the Dropouts meet multiple Additive Regression Trees (DART) algorithm as the boosting method within the context of the lightGBM framework [20].…”
Section: Framework For Development Of Predictive Models For Perceivedmentioning
confidence: 99%